Persepsi dan tahap kepuasan guru terhadap kepimpinan sekolah di bahagian Limbang, Sarawak - Lee, Yiing Chiong (1998)
A principal is responsible for demonstrating effective leadership in achieving the curriculum goals of the school. This research is meant to study the perception of teachers towards the leadership of their principals and their states of satisfaction. Three aspects of leadership that become the foci of this study are leadership in curriculum management, teaching and learning appraisal, as well as staff development programme management. A total of 242 teachers from all the seven government secondary schools in Limbang Division, Sarawak were chosen for this study.